Safety, efficacy, and selection strategy of laparoscopic local gastrectomy for gastrointestinal stromal tumors in the esophagogastric junction - Zhang, Haiqiao; Liu, Xiaoye; Zheng, Zhi; Yin, Jie; Zhang, Jun (Frontiers in Surgery, 2022)
Objective To investigate the safety, efficacy, and selection strategy of laparoscopic local gastrectomy for stromal tumors in the esophagogastric junction. Methods Thirty-eight patients with mesenchymal tumors in the esophagogastric junction were retrospectively enrolled from April 2018 to July 2021 in which the upper edge of the tumor is less than 2 cm from the Z-line or has invaded the Z-line <1/2 circumference. Surgical outcomes, complications, recover, and postoperative gastroesophageal reflux of both groups were compared. Results 27 patients underwent wedge resection, and 11 underwent resection by opening all of the layers of the stomach wall. Operative time (90.0 versus 181.8 min, respectively, P = 0.001) was shorter for the WR group versus RASW. Blood loss (20 versus 50 ml, respectively, P = 0.012) was less for the WR group versus RASW. Recovery of the RASW group was slower in terms of time to pass gas (2 versus 3 days, P = 0.034), time to oral intake (2 versus 4 days, P = 0.007), time to semi-liquid food intake (4 versus 8 days, P = 0.003), and postoperative hospitalization (5 versus 8 days, P = 0.001) versus WR. In terms of short-term complications (≤ 30 days), no significant between-group differences were observed. Cardia stenosis did not occur in either group. In the WR group, one patient experienced mild reflux at 6 months and recovered 1 year after surgery. In the RASW group, one patient experienced severe gastroesophageal reflux at 6 months and 1 year after surgery, which was not entirely relieved by taking antacids. No other patients have gastroesophageal reflux. Conclusion Laparoscopic local gastrectomy is safe and feasible for mesenchymal tumors in the esophagogastric junction in which the upper edge of the tumor is less than 2 cm from the Z-line or has invaded the Z-line <1/2 circumference, and has achieved an excellent short-term effect. The choice of surgery is based on the relationship between the tumor and the position of the cardia.